Variations in the structure and reactivity of thioester functionalized self-assembled monolayers and their use for controlled surface modification - Aped, Inbal; Mazuz, Yacov; Sukenik, Chaim N. (Beilstein Journal of Nanotechnology, 2012)
Thioester-functionalized, siloxane-anchored, self-assembled monolayers provide a powerful tool for controlling the chemical and physical properties of surfaces. The thioester moiety is relatively stable to long-term storage and its structure can be systematically varied so as to provide a well-defined range of reactivity and wetting properties. The oxidation of thioesters with different-chain-length acyl groups allows for very hydrophobic surfaces to be transformed into very hydrophilic, sulfonic acid-bearing, surfaces. Systematic variation in the length of the polymethylene chain has also allowed us to examine how imbedding reaction sites at various depths in a densely packed monolayer changes their reactivity. π-Systems (benzene and thiophene) conjugated to the thioester carbonyl enable the facile creation of photoreactive surfaces that are able to use light of different wavelengths. These elements of structural diversity combine with the utility of the hydrophilic, strongly negatively charged sulfonate-bearing surface to constitute an important approach to systematic surface modification.
Keywords: siloxane-anchored self-assembled monolayers; sulfonated interfaces; surface chemistry